Cardiac Arrest and Gastrointestinal Bleeding: A Case of Medical Heuristics - Tokunbo Ajayi; Jerome Okudo (Case Reports in Medicine)
Insufficient clinical data from patients is a major cause of errors in medical diagnostics. In an attempt to make a diagnosis, initial clinical information provided to the physician may be overly relied on as the only information required in making diagnosis leading to anchoring. Failure to rely on differential diagnoses in spite of new signs and symptoms or rethinking of initial hypothesis may lead to fixation on a certain diagnosis, which may lead to significant morbidity and mortality. In the event that there is an anchoring heuristic, like in our patient, it is important to consider differential diagnoses; however, it is not wrong to rely on some form of anchor. We report a case of a 62-year-old male with a history of multiple medical conditions and a history of acetaminophen overdose who presented to the hospital with large amounts of coffee ground emesis. He was subsequently transferred to the liver transplant center on discovery that he was in fulminant hepatic failure and died two days later in spite of aggressive medical treatment.